2013
DOI: 10.1155/2013/851621
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brazilian Plants Used to Treat Gastritis on the Oxidative Burst ofHelicobacter pylori-Stimulated Neutrophil

Abstract: Ten Brazilian medicinal plants used to treat gastritis and ulcers were carefully selected on the basis of ethnopharmacological importance and antiulcerogenic activity previously described. The antioxidant activity of the methanolic extracts was determined in analysis conditions that simulate a real biological activity on inhibition of the oxidative burst induced in neutrophils using Helicobacter pylori as activator, by a luminol-amplified chemiluminescence assay. The extracts, at low concentration (5 μg/mL), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
13
0
3
Order By: Relevance
“…Arg (Euphorbiaceae) are commonly used in folk medicine for the cure of gastric disorders . Recently, the antibacterial , anti-inflammatory (Lopes et al, 2010), antioxidant (Bonacorsi et al, 2013), antisecretory, gastroprotective, and anti-H. pylori effects of this species were reported. Alchornea triplinervia methanol extract was found to display antibacterial activity against the standard strain of H. pylori.…”
Section: Alchornea Triplinerviamentioning
confidence: 98%
“…Arg (Euphorbiaceae) are commonly used in folk medicine for the cure of gastric disorders . Recently, the antibacterial , anti-inflammatory (Lopes et al, 2010), antioxidant (Bonacorsi et al, 2013), antisecretory, gastroprotective, and anti-H. pylori effects of this species were reported. Alchornea triplinervia methanol extract was found to display antibacterial activity against the standard strain of H. pylori.…”
Section: Alchornea Triplinerviamentioning
confidence: 98%
“…It was demonstrated that 5-methoxy-3,4dehydroxanthomegnin from Paepalanthus latipes (Kitagawa, Bonacorsi, Da Fonseca, Vilegas, & Raddi, 2012), and the methanol extracts of Qualea parviflora and Qualea multiflora (Bonacorsi, Da Fonseca, Raddi, Kitagawa, & Vilegas, 2013) could inhibit H. pylori-induced oxidative burst in rats, and the latter two showed activities at low concentrations (5 μg/mL). In another study, methyl gallate from Byrsonima crassa showed the highest inhibitory effects on oxidative burst of H. pylori-stimulated neutrophils (IC 50 : 3.4 μg/mL), among all the phenolic compounds and methanol extract from B. crassa (Bonacorsi, Raddi, Da Fonseca, Sannomiya, & Vilegas, 2012).…”
Section: Anti-oxidative Stress Activitymentioning
confidence: 99%
“…M. elliptica leaves and/or bark have been used to treat gastric ulcers and gastritis, and they may also have an antimicrobial effect. These medicinal effects stem from stimulation of the immune system in response to pathogens (Moleiro et al, 2009;Vasconcelos et al, 2010b) and from the inhibition of the oxidative capacity of Helicobacter pylori (Bonacorsi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%